Evaluation of staff cultural awareness before and after attending cultural awareness training in an Australian emergency department - Chapman, Rose; Martin, C.; Smith, T. (2014)
Introduction: Cultural awareness of emergency department staff is important to ensure delivery of appropriate health care to people from all ethnic groups. Cultural awareness training has been found to increase knowledge about other cultures and is widely used as a means of educating staff, however, debate continues as to the effectiveness of these programs. Aim: To determine if an accredited cultural awareness training program affected emergency department staff knowledge, familiarity, attitude of and perception towards Australian Aboriginal and Torres Strait Islander people. Method: One group pre-test and post-test intervention study compared the cultural awareness of 44 emergency department staff towards Aboriginal and Torres Strait Islander people before and after training. The cultural awareness training was delivered in six hours over three sessions and was taught by an accredited cultural awareness trainer. Results: The cultural awareness training changed perception but did not affect attitude towards Aboriginal and Torres Strait Islander people in this group. Conclusion: Future strategies to improve staff cultural awareness need to be investigated, developed, implemented and evaluated.